URBANISMO MURCIANO DEL SIGLO XVIII: LAS REFORMAS DEL MALECÓN - Peñafiel Ramón, Antonio (Imafronte, 1993)
The reformations of el Malecón, planned as a part of the 18th century Murcian urban development and carried out in 1737, under the rule of Mayor D. Juan Francisco de Luján, converted this promenade into an interesring center of the social life of Murcia at that time. This may also be concluded from the city rules on the place. El Malecón combined its main function of defence against floods with a purely aesrhetic one, as a public promenade and place to enjoy at spare time. It was inscribed into a clearly baroque scenety and perspective; and, not to be forgotten, it was also given a kind of sacral atmosphere, a sign of which is the Triunfo raised ro commemorate one of the mostsignificant venerations of that period: the Inmaculate Conception of Maria.